Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru di Lembaga Islam - Maulid Agustin; Firmansyah (Universitas Muhammadiyah Prof Dr Hamka, 2023)
The purpose of this study is to describe the leadership role of school principals in improving teacher performance in Islamic educational institutions. The principal is one component in education that has an effect on improving teacher performance. The method used in this study uses a library research method or approach, literature or literature study, namely research conducted by reviewing and/or exploring several sources originating from scientific journals, literature and other information deemed relevant. The principal is a determinant of the success of an education because whether or not a quality is determined by the education provider and also the learning process depends on how the leadership in educational institutions is. The principal must be able to carry out the implementation and its functions, namely, the functions of educators, managers, administrators, supervisors, leaders, innovators, and motivators, figures and mediators. To achieve the success of an effective school or school, the teacher's performance must be properly measured and controlled. There are several factors that affect the performance of a teacher. This is where the role of the principal as a leader is needed because the principal is an agent of change, as a guide, spokesperson, and coach. So that the principal must create a healthy atmosphere in order to create a pleasant atmosphere and work spirit for teachers in order to improve the quality of a teacher's work in the teaching process.